Utilization of Black Soldier Fly (BSF) as Green Technology in Coconut Waste Management and Farmers’ Economic Empowerment - Farih, Muhammad; Lajaria, Ridha Taurisma; Djauhar, Asri; Tandipayuk, Grace Permatasari (Universitas Sulawesi Barat, 2025)
This study aims to analyze farmers’ perceptions, attitudes, and readiness to adopt the Black Soldier Fly (BSF) technology as an environmentally friendly innovation in coconut waste management in the Konawe Islands, Indonesia. A descriptive quantitative approach was used by surveying 45 coconut farmers in Pewalea village. Data were collected through structured questionnaires and analyzed using descriptive statistics with a Likert scale. The results indicate that 71.1% of farmers had never heard about BSF technology, while 77.8% expressed positive attitudes toward its implementation. A total of 55.6% were willing to adopt the technology if training and assistance were provided, and 64.4% identified access to capital as the main determinant of adoption. This study highlights the potential of BSF as a green innovation supporting circular economy practices and sustainable entrepreneurship in rural areas. The implication of this research is that the successful adoption of BSF technology requires integrated policies that strengthen farmers’ access to training, financial support, and market networks, which in turn can enhance rural economic resilience and environmental sustainability